The influence of mobile phone snubbing behavior on mobile phone addiction among adolescents in college education: the mediating role of peer and parent phone snubbing and self-control - Rongjie Zhou; Jinhua Chen; Gangjie Zhou; Yuhao Su; Tipeng Zhang (International Theory and Practice in Humanities and Social Sciences, 2025)
This study explores the link between adolescent mobile phone snubbing behavior and college students' mobile phone addiction, considering parental and peer snubbing behaviors and self-control as mediators. A survey of 510 college students in Henan Province revealed key findings. Adolescent snubbing behavior negatively correlates with self-control but positively with parental and peer snubbing, as well as mobile phone addiction. Self-control, in contrast, negatively correlates with these factors. Parental snubbing behavior positively correlates with peer snubbing and mobile phone addiction, while peer snubbing behavior also positively correlates with mobile phone addiction. Notably, self-control and peer snubbing behavior play significant mediating roles between adolescent snubbing behavior and mobile phone addiction. Adolescent snubbing behavior not only directly impacts mobile phone addiction but also indirectly through self-control and peer snubbing behavior. Although parental snubbing behavior does not directly mediate this relationship, it still influences it through these factors.